(untitled) - Wald, Susana (Hoboken, N.J., 2006)
Spanish For Dummies is the fun and easy way to learn Spanish quickly and painlessly! Written by the experts at the renowned Berlitz school, this hands-on resource shows you the ins and outs of the Spanish language and culture, acting as both a guidebook and a reference. Soon you will have all the tools you need to: Master the nuts and bolts of grammar; Greet others and introduce yourself; Get to know people with small talk; Order in restaurants; Shop anywhere; Go out on the town; Enjoy yourself with local recreation; Have a conversation on the phone; Work in an office and around the house; Ask for directions; Check in and out of a hotel; Use transportation; Call for help in an emergency.
Keywords: Spanish language,Spanish language; Textbooks for foreign speakers,Conversation